Kewenangan Pembentukan Kantor Dewan Perwakilan Daerah Repbulik Indonesia (DPD RI) Di Daerah Pemilihannya - Van Harling, Bryan Cristanto; Nendissa, Renny Heronia; Piris, Hendry John (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: 4 DPD-RI offices in their constituencies have only become definitive or owned by DPD RI but 30 other provinces are still using building loan facilities or leasing facilities owned by the Regional Government even though Law No. 17 of 2014 concerning MD3 article 252 describes the DPD RI office must be in the capital city province. Thus it is necessary to have procedures in establishing DPD offices in their constituencies.Purposes of the Research: This writing aims to describe the form of accountability for establishing DPD RI offices in each constituenc.Methods of the Research: The type of research used is normative, which is focused on providing explanations that explain a particular category. Approach the problem of the statute approach (statute approach) and the conceptual approach (conceptual approach). The collection of legal materials through primary legal materials is then free from secondary legal materials. Results of the Research: The procedure for establishing the RI DPD Office can be carried out through the following stages: a) Discussion of the RI DPD office; b) Discussion of Complementary Tools by PURT; c) Submission of the draft to DPD RI; d) Discussion of the development plan by Commission III of the DPR RI; e) Ratification of the DPD RI office construction plan; f) Discussion on the urgency of implementing development by PURT Complementary Tools; g) Cooperation with the Regional Government; h) Construction is underway.